THE METHOD OF ASSESSING THE QUALITY PARAMETERS OF INTERORGANIZATIONAL COORDINATION IN SUPPLY CHAINS - Richardovna Abramova, Elena; Olegovna Protsenko, Inga (Revista Inclusiones, 2020)
This article is aimed at studying the impact of logistical coordination frameworks — coplanning, harmonization of ruling documents, mutual approval of operational procurement procedures, resource integration — on the dynamics of quality indicators related to the procurement activities of supply chain participants. A method of assessing the quality parameters of interorganizational coordination in supply chains has been proposed, and the prospects for developing partnerships among the procurement process participants have been shown in conjunction with the comprehensive use of joint activity framework within integrated supply chains. Conclusions have been drawn on the impact of coordination framework on improving the competitiveness of partner enterprises: suppliers, manufacturers, transport, forwarding, and trade organizations. Comparative analysis, peer reviews, factor, and statistical analysis have been used in this study.